A review of reindeer lichen (Cladonia subgenus Cladina) linear growth rates - McMullin, Richard Troy; Rapai, Sean (Rangifer, 2020)
Cladonia subgenus Cladina (the reindeer lichens) can be a dominant part of terrestrial ecosystems worldwide. They are particularly abundant in arctic-alpine and boreal regions, where they are a primary food source for woodland caribou/reindeer in winter months. Determining the growth rates of reindeer lichen is important for understanding and managing lichen regeneration following disturbances such as timber harvesting, mining, grazing, and wildfire. Regeneration and rehabilitation rates can be calculated with greater accuracy when growth rates are well understood. We provide a summary of 17 studies from 6 countries that determined the linear growth rates of three reindeer lichen groups, Cladonia arbuscula/mitis (mean = 4.7 mm/yr.), C. rangiferina/ C. stygia (mean = 5.1 mm/yr.), and C. stellaris (mean = 4.8 mm/yr.). We use linear growth rates as a proxy for over-all growth and biomass. Variables found to influence lichen growth rates are also discussed, which include light, moisture, temperature, air pollution, acid rain, precipitation, snow accumulation, substrate, age of individuals, and type of disturbance. These results can assist land managers in developing more accurate strategies for restoring lichens in disturbed areas.